On the possibility of simultaneously achieving sufficient oxidation resistance and creep property at high temperatures exceeding 1000 °C in Co-based superalloys - Chen, Zhenghao; Okamoto, Norihiko L.; Chikugo, Kazuyoshi; Inui, Haruyuki (Journal of alloys and compounds, 2021)
Effects of additions of γ’ (L12)-forming elements (Ta, Ti and Ni; for creep property) and γ (FCC)-forming elements (Cr and Si; for oxidation resistance) on the microstructural stability, oxidation resistance and creep properties of two-phase γ/γ′ Co-based superalloys based on the Co–Al–W systems have been investigated in order to see whether simultaneous achievement of sufficient oxidation resistance and creep property for the usage above 1000 °C is possible or not for Co-based superalloys. A candidate composition ((Co0.8Ni0.2)-6Al–2W–2Ta–6Ti–8Cr–1Si) that provides relatively high γ′ solvus temperature and high γ′ volume fraction is found. The alloy with the candidate composition exhibits superior oxidation resistance when compared to Cr-free alloys but the creep property is not as good as expected from the high γ′ solvus temperature and high γ’ volume fraction and is only comparable to those of Ni-based superalloys of the first generation. The reason for the modest creep properties of the candidate alloy as well as possibilities for further investigation to simultaneously achieve sufficient oxidation resistance and creep property for Co-based superalloys are discussed. [Display omitted] •A new Co-based superalloy with improved oxidation and creep properties is developed.•A large amount of Cr is successfully added to the new alloy for oxidation resistance.•The alloy exhibits oxidation resistance better than any other alloys so far developed.•Ta and Ti are also co-added to the alloy for better creep property.•The alloy exhibits creep property comparable to 1st Gen. Ni-based superalloys.